1996
DOI: 10.1108/eb040605
|View full text |Cite
|
Sign up to set email alerts
|

Estimating non‐market costs in providing information services: developing an economic model

Abstract: The ‘holdings versus access’ dilemma encouraged the University of Leeds Library to undertake a project to compare the costs of periodical subscription and inter‐library lending. This article provides a brief synopsis of the project, which paid particular attention to calculating a cost for qualitative variables linked to ‘wait time’.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2002
2002

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…A detailed cost analysis profile in Getz's 1994 article identified the level of demand for the title in question as the crucial factor in any cost-benefit analysis. Work carried out at the University of Leeds (Wright 1996) concentrated on the level of variable non-market costs associated with provision of journal information via various routes. This research concluded that for every £20 increase in subscription cost the level of demand for the title had to increase by one per year to justify ownership of the title.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A detailed cost analysis profile in Getz's 1994 article identified the level of demand for the title in question as the crucial factor in any cost-benefit analysis. Work carried out at the University of Leeds (Wright 1996) concentrated on the level of variable non-market costs associated with provision of journal information via various routes. This research concluded that for every £20 increase in subscription cost the level of demand for the title had to increase by one per year to justify ownership of the title.…”
Section: Literature Reviewmentioning
confidence: 99%